Quantum transistor using superconducting qubits - Silva, Bruno Augusto Veloso Nunes (2022)
In recent times, quantum computation has become a flourishing field of research with increasing investment due to its promise to revolutionize computing, increasing the speed of information processing to levels far beyond the supercomputers available today. However, implementing these machines is not a simple task and several physical systems are proposed for developing quantum processors. One of the most promising plataforms and focus of this work are the artificial atoms built in superconducting circuits, also known as superconducting qubits (two-level quantum systems). In this master dissertation, we will describe how these superconducting circuits can be used as qubits. We will also apply Hamiltonian engineering techniques to study a system of two superconducting qubits coupled through a superconducting loop. The analysis of this system will allow us to demonstrate that it behaves as a quantum transistor, allowing to coherently transfer quantum information. To optimize the interactions in this system, we use the methods of effective dynamics, which will allow us to find the optimal parameters of the system and will allow us to understand in more detail its physics. Although it is standard to treat artificial atoms as simple qubits, we will show that such a simplification does not completely describe the dynamics of our transistor. It will be necessary to take in consideration the existence of the third energy level, so that the dynamics of the system can be adequately described. Our results reveal the fundamental importance that the most excited levels of superconducting qubits play in its dynamics, even if such states are never populated.